Improving Lecturer Performance Through Organizational Culture, Serving Leadership, Personality, And Work Motivation - Phetorant, Dimas; Isman Kadar; Lina Novita (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This research aims to find strategies to improve performance by analyzing the influence of organizational culture, servant leadership, personality, and work motivation. The research method used is quantitative. The sample consisted of 124 people from a population of 178 spread across twelve study programs using the proportional random sampling method. Path analysis and SITOREM are used in data analysis methodologies. Based on the analysis’s results, it was concluded that a) Organizational culture directly affects performance by 19.9%; b) Servant leadership directly affects performance by 14.4%; c) Personality directly affects performance by 10.6%; d) Work motivation directly affects performance by 6.9%; e) Organizational culture directly affects motivation at work by 23.1%; f) Servant leadership directly affects workplace motivation by 40.3%; g) Personality does not directly affect workplace motivation by 25.1%; h) Organizational culture has a 1.6% indirect impact on performance through work motivation; i) Servant leadership has a 2.8% indirect impact on performance through work motivation; and j) Personality has a 1.7% indirect impact on performance through work motivation.